New Insights into the Diversity of the Genus Faecalibacterium - Benevides, Leandro; Burman, Sriti; Martin, Rebeca; Robert, Véronique; Thomas, Muriel; Miquel, Sylvie; Chain, Florian; Sokol, Harry; Bermudez-Humaran, Luis G.; Morrison, Mark; Langella, Philippe; Azevedo, Vasco A.; et al. (Frontiers in Microbiology, 2017)
Faecalibacterium prausnitzii is a commensal bacterium, ubiquitous in the gastrointestinal tracts of animals and humans. This species is a functionally important member of the microbiota and studies suggest it has an impact on the physiology and health of the host. F. prausnitzii is the only identified species in the genus Faecalibacterium, but a recent study clustered strains of this species in two different phylogroups. Here, we propose the existence of distinct species in this genus through the use of comparative genomics. Briefly, we performed analyses of 16S rRNA gene phylogeny, phylogenomics, whole genome Multi-Locus Sequence Typing (wgMLST), Average Nucleotide Identity (ANI), gene synteny, and pangenome to better elucidate the phylogenetic relationships among strains of Faecalibacterium. For this, we used 12 newly sequenced, assembled, and curated genomes of F. prausnitzii, which were isolated from feces of healthy volunteers from France and Australia, and combined these with published data from 5 strains downloaded from public databases. The phylogenetic analysis of the 16S rRNA sequences, together with the wgMLST profiles and a phylogenomic tree based on comparisons of genome similarity, all supported the clustering of Faecalibacterium strains in different genospecies. Additionally, the global analysis of gene synteny among all strains showed a highly fragmented profile, whereas the intra-cluster analyses revealed larger and more conserved collinear blocks. Finally, ANI analysis substantiated the presence of three distinct clusters – A, B, and C – composed of five, four, and four strains, respectively. The pangenome analysis of each cluster corroborated the classification of these clusters into three distinct species, each containing less variability than that found within the global pangenome of all strains. Here, we propose that comparison of pangenome subsets and their associated α values may be used as an alternative approach, together with ANI, in the in silico classification of new species. Altogether, our results provide evidence not only for the reconsideration of the phylogenetic and genomic relatedness among strains currently assigned to F. prausnitzii, but also the need for lineage (strain-based) differentiation of this taxon to better define how specific members might be associated with positive or negative host interactions.